MAKNA DAN IDEOLOGI KOMUNITAS SEPEDA KEBO DI SURABAYA DALAM KAJIAN SUBKULTUR - Pariyanto Pariyanto (Lakon : Jurnal Kajian Sastra dan Budaya, 2015)
The rising popularity of modern bikes has replaced sepeda kebo (Indonesia’s old-fashioned bike) as one of common means of transportation in Indonesia. Sepeda kebo nowadays is considered as antique that implicates on impression of sepeda kebo riding as nonmainstream activities. The riders belong to sepeda kebo cliques that introduce community-scaled companionship of riders. By implementing phenomenological paradigm, this qualitative research is motivated by three research questions: first, to investigate the significance of sepeda kebo clique for the members; second, to explore the importance of sepeda kebo clique membership for the members; and third, to illuminate the characterizing orientations initiated and evolved within sepeda kebo cliques in order to either promote the cliques as subculture or defining them as communal unit of interest. The research strategy consists of purposive sampling technique, participatory observation and in-depth interview as data collection method and Creswell’s procedure as data analysis sequence.Sepeda kebo cliques in Surabaya are subcultures in globalization era and are forms of hybrid identity in coping with and resisting to mainstream cultures.